2003
DOI: 10.1103/revmodphys.75.237
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion in metallic glasses and supercooled melts

Abstract: Amorphous metallic alloys, also called metallic glasses, are of considerable technological importance. The metastability of these systems, which gives rise to various rearrangement processes at elevated temperatures, calls for an understanding of their diffusional behavior. From the fundamental point of view, these metallic glasses are the paradigm of dense random packing. Since the recent discovery of bulk metallic glasses it has become possible to measure atomic diffusion in the supercooled liquid state and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
346
2
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 577 publications
(379 citation statements)
references
References 187 publications
27
346
2
4
Order By: Relevance
“…[22]). Furthermore, the diffusion of alloying elements in metallic glasses is known to be sensitive to the relative size of the diffusing atoms and the host atoms [23]. Higher diffusivity of the smaller Ni compared to the larger La in the amorphous Al-based matrix supports the hypothesis of preferred uptake of Ni from the amorphous phase intothe Al crystallites during ball milling.…”
Section: Lattice Parametersupporting
confidence: 48%
“…[22]). Furthermore, the diffusion of alloying elements in metallic glasses is known to be sensitive to the relative size of the diffusing atoms and the host atoms [23]. Higher diffusivity of the smaller Ni compared to the larger La in the amorphous Al-based matrix supports the hypothesis of preferred uptake of Ni from the amorphous phase intothe Al crystallites during ball milling.…”
Section: Lattice Parametersupporting
confidence: 48%
“…20 At lower temperatures, hopping over barriers in the energy landscape requires large atomic amplitudes that can be provided by localised soft vibrations. 18 At higher temperatures, there is an increase in both the atomic displacements and the number of atoms participating in the jumps. 21 It is pertinent to note that, although crystallisation is universally known to be a first-order thermodynamic transformation, 22,23 glass transition has been prevailingly considered as a largely dynamical phenomenon 24 and soft phonons are known to be related to the dynamics of amorphous alloys.…”
Section: Resultsmentioning
confidence: 99%
“…21 It is pertinent to note that, although crystallisation is universally known to be a first-order thermodynamic transformation, 22,23 glass transition has been prevailingly considered as a largely dynamical phenomenon 24 and soft phonons are known to be related to the dynamics of amorphous alloys. 18,25 Although the energy landscape curvature and mean-squared atomic displacements (MSD) are two different quantities, they are inter-connected often in complicated relations. The calculated MSD of Mg atoms in the vicinity of glass transition temperature 15 Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…Such jumps give e. g. rise to the telegraph noise in point contacts and are thought to be the elementary process in diffusion [50]. In our previous study of relaxations in the soft sphere glass we found them to be closely correlated to the quasi-localized vibrations.…”
Section: Relaxationsmentioning
confidence: 97%